Love withdrawal predicts electrocortical responses to emotional faces with performance feedback: a follow-up and extension - Huffmeijer, Renske (BioMed Central, 2014)
BACKGROUND: Parental use of love withdrawal is thought to affect children’s later psychological functioning because it creates a link between children’s performance and relational consequences. In addition, recent studies have begun to show that experiences of love withdrawal also relate to the neural processing of socio-emotional information relevant to a performance-relational consequence link, and can moderate effects of oxytocin on social information processing and behavior. The current study follows-up on our previous results by attempting to confirm and extend previous findings indicating that experiences of maternal love withdrawal are related to electrocortical responses to emotional faces presented with performance feedback. RESULTS: More maternal love withdrawal was related to enhanced early processing of facial feedback stimuli (reflected in more positive VPP amplitudes, and confirming previous findings). However, attentional engagement with and processing of the stimuli at a later stage were diminished in those reporting higher maternal love withdrawal (reflected in less positive LPP amplitudes, and diverging from previous findings). CONCLUSIONS: Maternal love withdrawal affects the processing of emotional faces presented with performance feedback differently in different stages of neural processing.